Parco Biamonti a San Biagio della Cima: dal parco letterario al parco produttivo, dal territorio che si fa letteratura ad una nuova letteratura del territorio - Alborno, Pietra; Della Puppa, Federico; Traldi, Camilla (Scienze del Territorio, 2018)
The creation of the literary itinerary dedicated to Francesco Biamonti in San Biagio della Cima, in 2015, has become the chance to think about the landscape as inspired by the ‘productive protection’ concept proposed by Massimo Quaini. From this concept was born the idea of the ‘productive park’, as an alternative approach to promote the landscape and its producers starting from the legacy of Biamonti and his analytical gaze, instead of the well-known - but sometimes too conservative - naturalistic approach. The methodological requirement is the ‘individual’ characterisation of San Biagio landscape, an approach that, starting from the single case study, could be extended to any rural landscape and to its relative policies of enhancement and protection, arguments that are more and more current nowadays.